Rancang Bangun Alat Pembersih Bearing Menggunakan Gelombang Suara Ultrasonik - Harlan Effendi; Ibrahim Newton (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
This device works by providing electrical waves to the Transducer with compatible frequency and power (40kHz and 60W), cavitation appear due to sound vibrations in the liquid that reach the gap in the bearing so the dirt will cleaned off the bearing. Parameters that are measured and tested is the wave generated by Arduino ProMini microcontroller, the wave that enters the amplifier, the wave received by Transducer, and result of cleaning. From testing process, it produces frequency with accuracy of 82.5% and able to drive the Transducer even though not yet at maximum power due to poor transformer quality.